Expressions and Clinical Significance of Met and YAP in Gastric Cancer Tissue Microarray - Jinxia Li; Xinyun Zhang; Ying Liu; Jinyong Zhou; Li Shen; Guangxin Yue (Gastroenterology Research and Practice)
Objective. This study is aimed at investigating the expression of Met and YAP in gastric cancer and their impact on clinical prognosis. Methods. Tissue samples and clinical data were collected from 89 patients with gastric cancer. Immunohistochemistry was performed to quantify the expression of Met and YAP using tissue microarray. The correlation between the expressions of Met, YAP, and clinicopathological characteristics of patients was determined using a chi-square test. Survival analysis was conducted using the Kaplan-Meier method, while multivariate survival analysis was performed using the Cox proportional hazard model. Bioinformatics analysis was carried out by downloading chip data from TCGA. Results. The expression levels of both Met and YAP were significantly higher in gastric cancer tissues compared to adjacent tissues (P<0.001). Met expression showed a positive association with P53 and CD133, whereas YAP expression correlated positively with tumor grade and CD133 (P<0.05). Pearson’s analysis revealed a significant correlation between Met expression and VEGFR as well as CD133, while YAP expression correlated with Ki67 and VEGFR (P<0.05). Patients with high levels of both Met and YAP exhibited decreased survival time (P<0.01). Furthermore, Met expression, N stage, and VEGFR were identified as independent risk factors for gastric cancer prognosis (P<0.05), whereas no such association was observed for YAP expression. Bioinformatics analysis demonstrated a significant correlation between the expressions of Met and YAP; both proteins were highly expressed in gastric cancer patients accompanied by markedly reduced survival time. Conclusion. The expressions of Met and YAP are closely associated with the survival outcomes as well as clinicopathological features in patients with gastric cancer. Moreover, our findings highlight that Met serves as an independent prognostic factor for gastric cancer.